(untitled) (Indian Journal of Animal Production and Management, 2015)
A study was conducted to assess the effect of sex on growth attributes such as body weight, body length, heart girth and height at wither growth in Naga local pig at birth, weaning and adult stage. These attributes were collected through measurement and field survey. The results revealed that there was significant difference between the male and female in different age groups except body weight at weaning and heart girth at weaning and at adult stage. Growth parameters were significantly higher in male than in female animal in three stages.